INNOVATION OF FISH CRACKER PRINTING MACHINE FOR PRODUCTION PROCESS EFFICIENCY - Alghifari, Muhammad Romadhon; Murnawan, Hery (Jurnal Disprotek, 2025)
UMKM Rejeki Barokah which is engaged in the production of mackerel fish crackers with the brand "Tujuh Bintang," faces the constraint of limited production capacity due to the manual process that takes a long time. This study aims to design and implement a cracker printing machine to increase production efficiency without reducing product quality. The methods used include literature studies, direct observation, interviews, and collection of quantitative data from the production process and market needs. The design of the machine is based on worker anthropometric data, including hand reach length of 59 cm, knee height of 54 cm, and standing elbow height of 79 cm, to ensure ergonomics of use. The results of the study showed that the printing machine was able to speed up the dough printing process from 8 minutes per kilogram to 4.54 minutes per kilogram, increase production capacity to 1,890 kilograms per month, meet market demand, and increase the operational efficiency of UMKM. Production costs (HPP) were recorded at IDR 48,511 per kilogram, resulting in a profit of IDR 11,489 per kilogram. The implementation of this machine not only helps meet market needs but also strengthens the competitiveness of MSMEs through time efficiency, reduced labor costs, and increased productivity. With these results, the printing machine becomes a strategic solution to support the sustainability of Rejeki Barokah MSME businesses in an increasingly competitive market. INOVASI MESIN CETAK KERUPUK IKAN GUNA EFFISIENSI PROSES PRODUKSIUMKM Rejeki Barokah, yang bergerak dalam produksi kerupuk ikan tenggiri dengan merek "Tujuh Bintang," menghadapi kendala keterbatasan kapasitas produksi akibat proses manual yang memakan waktu lama. Penelitian ini bertujuan merancang dan menerapkan mesin cetak kerupuk untuk meningkatkan efisiensi produksi tanpa mengurangi kualitas produk. Metode yang digunakan meliputi studi literatur, observasi langsung, wawancara, dan pengumpulan data kuantitatif dari proses produksi dan kebutuhan pasar. Perancangan mesin dilakukan berdasarkan data antropometri pekerja, meliputi panjang jangkauan tangan 59 cm, tinggi lutut 54 cm, dan tinggi siku berdiri 79 cm, untuk memastikan ergonomi penggunaan.Hasil penelitian menunjukkan bahwa mesin cetak mampu mempercepat proses pencetakan adonan dari 8 menit per kilogram menjadi 4,54 menit per kilogram, meningkatkan kapasitas produksi hingga 1.890 kilogram per bulan, memenuhi permintaan pasar, serta meningkatkan efisiensi operasional UMKM. Biaya produksi (HPP) tercatat sebesar Rp 48.511 per kilogram, menghasilkan keuntungan Rp 11.489 per kilogram. Implementasi mesin ini tidak hanya membantu memenuhi kebutuhan pasar tetapi juga memperkuat daya saing UMKM melalui efisiensi waktu, pengurangan biaya tenaga kerja, dan peningkatan produktivitas. Dengan hasil ini, mesin cetak menjadi solusi strategis untuk mendukung keberlanjutan usaha UMKM Rejeki Barokah di pasar yang semakin kompetitif.